On-site rapid detection of toxic Alexandrium tamiyavanichii: integrating the species-specific hydrolysis probe in insulated isothermal polymerase chain reaction (iiPCR) - Nyuk, Fong Kon; Lik, Winne Sing Lau; Ing, Kuo Law; Po, Teen Lim; Chui, Pin Leaw (Springer Netherlands, 2016)
On-site investigation of phytoplankton samples is important for rapid detection of harmful algal species and for early warning of harmful algal bloom. Molecular detection method by DNA amplification in a portable insulated isothermal PCR (iiPCR) device provides a simple and rapid detection based on fluorescent probe within an hour of reaction time. The assay was developed for a paralytic shellfish toxinproducing dinoflagellate Alexandrium tamiyavanichii. The assay presents the data as positive or negative on the presence or absence of A. tamiyavanichii cells, with a limit of detection (LOD) at five target cells per reaction. While the assay is incapable to accurately quantify cell density, it exhibits high detection accuracy and strongly correlated with quantitative PCR (qPCR) data. The user repeatability of iiPCR assay was evaluated; the results showed that no significant differences in the assay run by different operators. Field applicability of the assay was further validated by environmental samples. Despite the shortcoming of the assay, the overall performance of the assay to detect cells, its low-cost effectiveness, and portability for on-site detection, iiPCR has proven its potential as an early screening tool for harmful algae monitoring.